Optimistic workplace : creating an environment that energizes everyone - Murphy, Shawn (New York AMACOM--American Management Association, 2016)
The book states a case, debunks the myths, and yes, talks about the dangers of excess in relationship to optimism. Then it lays out a set of steps that any of us can follow to create a more energized, optimistic workplace.